2022
DOI: 10.2147/rru.s374068
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Prognostic Factors of Patients with Urothelial Carcinoma Undergoing Radical Cystectomy and pT0 in the Final Histology Without Neoadjuvant Chemotherapy

Abstract: Absence of tumor in the final histopathology after radical cystectomy (RC) is a rare but potentially favorable outcome. Therefore, we aimed to analyze outcomes and prognostic factors of patients with urothelial carcinoma (UC) undergoing RC and T0 in the final histology without neoadjuvant chemotherapy at a high-volume academic center. Patients and Methods: We retrospectively analyzed patients undergoing RC for pure UC between 2004 and 2020. Cancer-specific survival (CSS) and overall survival (OS) were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The rationale behind performing TURBT alone lies in the possibility of pathologic absence of tumor (pT0) at RC. Recent RC series reported that the expected incidence of pT0 without neoadjuvant chemotherapy ranged from 6% to 20% [6][7][8]. RC is indisputably the best approach, even in patients with bladder cancer with pT0 disease, but patients may have missed the opportunity for bladder preservation.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale behind performing TURBT alone lies in the possibility of pathologic absence of tumor (pT0) at RC. Recent RC series reported that the expected incidence of pT0 without neoadjuvant chemotherapy ranged from 6% to 20% [6][7][8]. RC is indisputably the best approach, even in patients with bladder cancer with pT0 disease, but patients may have missed the opportunity for bladder preservation.…”
Section: Introductionmentioning
confidence: 99%